Arteriovenous fistula with basilic vein elevation. Case series - Silva Rodríguez, Oswaldo (2022)
Arteriovenous fistula (AVF) is necessary for hemodialysis access. The preferred configurations are radial-cephalic, brachial-cephalic, and brachial-basilic with elevation or transposition and tunneling. The purpose of this study was to present our experience for creating arteriovenous fistulae using the elevation of the basilic vein technique. Between June 2017 and March 2020, thirteen brachial–basilic fistulae with elevation of the basilic vein were performed in seven male and six female subjects. Their mean age was 65.7 years. During the early post-op period, there were two cases of forearm hematoma, wound infection in two cases, and edema in one case. During the follow-up period, three fistulae did not have a good progression, and three patients died; the remaining AVFs are still working. In conclusion, brachial–basilic AVF with elevation of the basilic vein is an alternative in patients who have already exhausted other access options.